2013
DOI: 10.1016/j.bbalip.2012.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Drug induced phospholipidosis: An acquired lysosomal storage disorder

Abstract: There is a strong association between lysosome enzyme deficiencies and monogenic disorders resulting in lysosomal storage disease. Of the more than 75 characterized lysosomal proteins, two thirds are directly linked to inherited diseases of metabolism. Only one lysosomal storage disease, Niemann-Pick disease, is associated with impaired phospholipid metabolism. However, other phospholipases are found in the lysosome but remain poorly characterized. A recent exception is lysosomal phospholipase A2 (group XV pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(132 citation statements)
references
References 76 publications
2
127
1
2
Order By: Relevance
“…The elevated amount of intracellular phospholipids has previously been interpreted as an adaptive response to prevent the toxicity of foreign matter by sequestering them away from other cellular sites (Shayman & Abe, 2013). However, in our study, we observed ultrastructural and metabolic changes indicating significant cellular alteration that can be deleterious even at non-cytotoxic concentrations and can affect the main function of ATII cells, which is the production of lung surfactant.…”
Section: Discussioncontrasting
confidence: 52%
“…The elevated amount of intracellular phospholipids has previously been interpreted as an adaptive response to prevent the toxicity of foreign matter by sequestering them away from other cellular sites (Shayman & Abe, 2013). However, in our study, we observed ultrastructural and metabolic changes indicating significant cellular alteration that can be deleterious even at non-cytotoxic concentrations and can affect the main function of ATII cells, which is the production of lung surfactant.…”
Section: Discussioncontrasting
confidence: 52%
“…CAD drugs that cause phospholipidosis-such as amiodarone-have been associated with hepatic injury and fibrosis in animal models (Ágoston et al, 2003). Recent data provide evidence that sequestration of drugs in lysosomes can lead to significant cellular dysfunction, including impaired lysosomal protein degradation (Shayman and Abe, 2013), which is consistent with the alterations in the protein ubiquitination pathway suggested by the results in this study. Interestingly, concentrations of the parent compound in the blood at 2 and 24 h after treatment did not correlate with liver injury in PF-04287881-treated animals.…”
Section: Discussionsupporting
confidence: 90%
“…Lysosomal trapping of drugs has also been associated with druginduced phospholipidosis, an iatrogenic lysosomal storage disorder characterized by the accumulation of phospholipids in tissues (Daniel and Wojcikowski, 1999;Anderson and Borlak, 2006;Hanumegowda et al, 2010;Shayman and Abe, 2013). At least 385 drugs that cause phospholipidosis have been identified in the Food and Drug Administration database (Advisory Committee for Pharmaceutical Science, April 2010; http://www.fda.gov/downloads/advisorycommittees/committeesmeetingmaterials/drugs/advisorycommitteeforpharmaceuticalscienceandclinicalpharmacology/ucm210798.pdf), all of which have been identified as CADs.…”
Section: Discussionmentioning
confidence: 99%